2003
DOI: 10.1590/s1519-38292003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections control in the context of the IMCI strategy in the Americas

Abstract: Acute respiratory infections (ARI) are an important cause of morbidiyty and mortality in children all over the World, particularly in developing countries. Contrasts in mortality can be observed among the countries in America, and also within the countries. Contrasts are also observed in morbidity, associated with differences in nutritional status, absence of breast-feeding and characteristics of care given for ill chidren. Parents perception of disease, patterns and habits of care administered to child during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
(62 reference statements)
1
8
0
4
Order By: Relevance
“…These percentages were also found in several other studies 3,21,22. Individual factors, such as immunological immaturity and the anatomical characteristics of the respiratory tree, along with life habits that predispose to exposure to infectious and irritating agents affecting the respiratory tract, explain the vulnerability of the pediatric age group to respiratory diseases 23,24. In addition to standing out as the most frequent condition, this study observed CIs for those causes increased in the city and decreased in Brazil, for the three appraised age groups.…”
Section: Discussionsupporting
confidence: 68%
“…These percentages were also found in several other studies 3,21,22. Individual factors, such as immunological immaturity and the anatomical characteristics of the respiratory tree, along with life habits that predispose to exposure to infectious and irritating agents affecting the respiratory tract, explain the vulnerability of the pediatric age group to respiratory diseases 23,24. In addition to standing out as the most frequent condition, this study observed CIs for those causes increased in the city and decreased in Brazil, for the three appraised age groups.…”
Section: Discussionsupporting
confidence: 68%
“…Children younger than five years old, who become ill and use the health care system, frequently suffer from respiratory infections. Acute respiratory infection (ARI) is the most common manifestation, and it is responsible for high morbidity and mortality rates, especially in developing countries [1][2][3]. A study conducted in Sao Paulo city in 1996 revealed that 27.7% of hospitalized children within that age group had ARI [1].…”
mentioning
confidence: 99%
“…The management of acute respiratory infection has been a priority in recent decades, with the implementation of control and prevention programs 5,7,[28][29][30] . Training in Integrated Management of Childhood Illness (IMCI) to classify diseases that really require antibiotics can be critical for better care.…”
Section: Discussionmentioning
confidence: 99%